2023
DOI: 10.3389/fendo.2023.1166117
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the serum triglyceride-glucose index and pericoronary adipose tissue attenuation and plaque features using dual-layer spectral detector computed tomography: a cross-sectional study

Abstract: Background and aimsThe triglyceride-glucose (TyG) index is a reliable alternative marker for insulin resistance (IR). Pericoronary adipose tissue (PCAT) can indirectly reflect coronary inflammation. IR and coronary inflammation play a key role in the development and progression of coronary atherosclerosis. Therefore, this study investigated the relationships between the TyG index, PCAT and atherosclerotic plaque characteristics to explore whether IR might lead to coronary artery atherosclerosis progression by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…Simultaneously, our research demonstrates that individuals with an increased serum TyG index also frequently have high-risk plaques (HRPs) and typical HRPCs. This result is in line with other research (23,37), showing a relationship between plaque stability and the TyG index. Thus, we hypothesize that serum TyG index level and plaque instability may be related.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Simultaneously, our research demonstrates that individuals with an increased serum TyG index also frequently have high-risk plaques (HRPs) and typical HRPCs. This result is in line with other research (23,37), showing a relationship between plaque stability and the TyG index. Thus, we hypothesize that serum TyG index level and plaque instability may be related.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, this research also evaluated the correlation between the TyG index and adverse plaque characteristics (HRPCs) and the FAI in hypertensive patients. Damage to vascular endothelial cells brought on by IR can trigger an inflammatory reaction ( 23 ). It has been demonstrated that coronary artery inflammation inhibits fat formation in perivascular fat, thereby altering the attenuation of perivascular fat to CCTA ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 As an alternative to the conventional gold standard hyperinsulinemic‐euglycemic clamp method, the TyG index was introduced as a more simple and cost‐effective means of IR with high sensitivity (96.5%) and specificity (85%). 14 Currently, the TyG index has been extensively explored in diverse medical issues, such as cardiovascular disease, 6 , 7 , 8 , 9 arterial stiffness progression, 10 diabetic nephropathy, 11 new‐onset hypertension, 15 cardiometabolic diseases, 16 DM, 17 , 18 , 19 intensity care unit mortality, 20 obesity, 21 and hearing impairment. 22 However, there are relative few reports about TyG index and hypertensive nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the triglyceride glucose (TyG) index has emerged as a non‐invasive and cost‐effective alternative indicator to assess IR. 5 Recent studies have shown that an elevated TyG index is associated with an increased risk of cardiovascular disease, 6 , 7 , 8 , 9 arterial stiffness progression, 10 and diabetic nephropathy. 11 However, evidence supporting the association between the TyG index and hypertension‐induced renal injury remains limited.…”
Section: Introductionmentioning
confidence: 99%